UNIT 30.3 Pulse‐Chase Analysis for Studying Protein Synthesis and Maturation. (3rd November 2014) - Fritzsche, Susanne; Springer, Sebastian
Abstract : Pulse‐chase analysis is a well‐established and highly adaptable tool for studying the life cycle of endogenous proteins, including their synthesis, folding, subunit assembly, intracellular transport, post‐translational processing, and degradation. This unit describes the performance and analysis of a radiolabel pulse‐chase experiment for following the folding and cell surface trafficking of a trimeric murine MHC class I glycoprotein. In particular, the unit focuses on the precise timing of pulse‐chase experiments to evaluate early/short‐time events in protein maturation in both suspended and strictly adherent cell lines. The advantages and limitations of radiolabel pulse‐chase experiments are discussed, and a comprehensive section for troubleshooting is provided. Further, ways to quantitatively represent pulse‐chase results are described, and feasible interpretations on protein maturation are suggested. The protocols can be adapted to investigate a variety of proteins that may mature in very different ways. © 2014 by John Wiley & Sons, Inc.